2022
DOI: 10.5935/0004-2749.20230043
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of meibomian gland dysfunction in patients with rosacea

Abstract: To compare ocular surface parameters in rosacea patients with those of controls. Methods: Ninety-three participants took part in this cross-sectional, observational, non-interventional study. These consisted of a rosacea group (n=40) and a control group (n=53). We compared objective parameters of the ocular surface, including conjunctival hyperemia, tear film stability and volume, meibomian gland dysfunction, dry eye disease, and ocular surface staining, between the two groups. Results: In the rosacea group, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In humans, it has been shown that the act of blinking leads to the expression of meibum lipids. Forceful blinking increases the amount of meibum released onto the ocular surface whereas incomplete blinking leads to decreased meibum expression, decreased TFBUT, and, subsequently, an increased incidence of MGD 59–61 . Thus, a similar phenomenon may be occurring in brachycephalic animals with an incomplete blink.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, it has been shown that the act of blinking leads to the expression of meibum lipids. Forceful blinking increases the amount of meibum released onto the ocular surface whereas incomplete blinking leads to decreased meibum expression, decreased TFBUT, and, subsequently, an increased incidence of MGD 59–61 . Thus, a similar phenomenon may be occurring in brachycephalic animals with an incomplete blink.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Additional risk factors of EDED in humans include comorbidities, such as ocular rosacea, 59 local hypersensitivity reactions to or the toxic effects of medications, such as retinoic acid, 60 and marginal blepharitis. However, to date, no studies have identified these additional factors to cause EDED in dogs, thus additional work is needed to investigate their potential role.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…In rosacea, meibomian gland hypersecretion occurs with a turbid consistency to the meibum leading to the plugging of the MG and chalazion formation. Ocular rosacea also causes significant meibomian gland loss that can objectively be demonstrated with meibography [ 15 , 16 ]. This also culminates in an abnormal tear film, with a soapy, inferior tear meniscus, leading to evaporative dry eye.…”
Section: Ocular Rosaceamentioning
confidence: 99%